Tourism and protected areas : benefits beyond boundaries : the Vth IUCN World Parks Congress / [Edited by] Robyn Bushell, Paul F J Eagles - Eagles, Paul F. Jedited
This book focuses on the tourism issues discussed at the Vth IUCN World Parks Congress. The book reflects the past 10 years of global challenges in tourism and the lessons learnt in protected area management. It shows the significant achievements of tourism in contributing to sustainable ecosystem development and projects issues for the next decade. It will be of interest to researchers in tourism and protected areas, practitioners, bureaucrats, managers and conservationists. The book has 21 chapters and a subject index